Neuropsychiatric involvement in juvenile systemic lupus erythematosus - Demirkaya, Erkan; Bakkaloğlu, Ayşin; Beşbaş, Nesrin; Topaloğlu, Rezan; Türker, Türker; Işikhan, Vedat; Karli-Oğuz, Kader; Yalnizoğlu, Dilek; Aktay-Ayaz, Nuray; Bilginer, Yelda; Ozen, Seza (The Turkish Journal of Pediatrics, 2008)
Neuropsychiatric involvement is an important cause of morbidity and mortality in systemic lupus erythematosus (SLE) and it has been reported to occur in 22-95% of the childhood SLE patients. The aim of this study was to evaluate the neuropsychiatric involvement in our juvenile SLE patients. This was a cross-sectional assessment of patients to investigate the relationship between the involvement of the nervous system and the clinical factors, including autoantibodies, renal involvement and disease activity. We used Symptom Checklist-90-R (SCL-90-R), designed to measure the psychopathological symptoms. As controls, we used 20 healthy adolescents and 20 patients with chronic diseases without any neuropsychiatric manifestations. Overall, 55% (n= 11) of the patients displayed neurological symptoms and/or signs. However, central nervous system (CNS) imaging showed pathological findings only in four of these patients. Patients with headache only had normal CNS imaging. Nine patients had moderate to severe depression. When SLE patients were compared to healthy controls and to adolescents with chronic diseases, they were found to be significantly more depressed. In conclusion, pediatric rheumatologists should be aware of the frequency of neuropsychiatric disturbances in SLE. The neuropsychiatric disorders do not always correlate with disease activity and these children need professional psychological evaluation.